Social Effects of Kijing International Harbor’s Building on Locals’ Life in Sungai Kunyit Village - Desca Thea Purnama; Chainar Chainar (Indonesian Journal of Multidisciplinary Science, 2022)
The construction of Kijing International Port which is being built by the government in the Sungai Kunyit District area of Mempawah Regency is one of the ports that will become the entrance of trade import exports. Port Development in the Kijing region is one of the government's programs to accelerate the provision of national infrastructure as stated in Presidential Regulation No. 56 of 2018 concerning the Second Amendment to Presidential Regulation No. 3 of 2016 concerning the Acceleration of the Implementation of National Strategic Projects. The existence of the construction of the Kijing international port indirectly poses risks or consequences to the government and also the communities around the development area. The impact generated by the development is not only the economic impact but also the social impact received on the construction of the Kijing international port. The purpose of this study is to describe and analyze the social impacts that occur due to the construction of Kijing International Port in the Sungai Kunyit Subdistrict area. The research method used is a type of qualitative research with a descriptive summary. As for the output of this research, this research is expected to be used as a book and entered into accredited journals.